A halloysite nanotube curing accelerator with imidazole compound bonded to surface, method for manufacturing thereof and epoxy resin composition containing the same
Patent Information
- Application Number
- KR1020230104200
- Authority / Receiving Office
- KR · KR
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2023-08-09
- Publication Date
- 2026-09-11
- Estimated Expiration
- 2043-08-09
Smart Images

Figure 112023087763785-PAT00021_ABST
Abstract
Description
Technology Field
[0001] The present invention relates to a halosite nanotube curing accelerator in which an imidazole-based compound is bonded to the surface via urethane bonding, a method for manufacturing the same, and an epoxy resin composition comprising the same. Background Technology
[0002] Epoxy resin compositions are widely applied in various industrial fields, such as coatings, fiber-reinforced composites, and automobiles, due to their advantages including excellent weather resistance, high mechanical strength, excellent heat resistance, and high adhesion. In particular, as their utilization for lightweighting materials in the automotive and aerospace sectors has increased recently, the need for accessible and rapid curing processes has grown, leading to a rising demand for epoxy resins capable of curing at room or low temperatures.
[0003] Conventional epoxy curing agents mainly use imidazole-based, acid anhydride-based, and trivalent amine-based compounds, but epoxy resin compositions containing these require high energy during the curing process and have limitations such as requiring a long pot life at low temperatures.
[0004] Therefore, there is a continuous demand for a method to manufacture a new curing accelerator that not only possesses excellent mechanical properties in a cured product of an epoxy resin composition but also satisfies low curing temperatures and short pot life during the curing process.
[0005] Halloysite nanotubes (HNTs) are naturally occurring tubular aluminosilicate materials that can exhibit high mechanical and thermal properties when added in small amounts to polymer composites. Furthermore, due to their naturally occurring cylindrical shape, they have the advantage of being cheaper than carbon nanotubes. Accordingly, a method of surface modification by substituting naturally occurring hydroxyl groups on halloysite nanotubes is also used. The problem to be solved
[0006] The present invention aims to provide a halloysite nanotube curing accelerator in which an imidazole-based compound is bonded to the surface.
[0007] In addition, the present invention aims to provide a method for manufacturing the halloysite nanotube curing accelerator.
[0008] In addition, the present invention aims to provide an epoxy resin composition that includes the halloysite nanotube curing accelerator, thereby maintaining excellent mechanical properties while exhibiting excellent curing behavior. means of solving the problem
[0009] The present invention provides a halloysite nanotube curing accelerator in which an imidazole-based compound is bonded to the surface by urethane bonding.
[0010] In one embodiment, the imidazole-based compound may have an isocyanate group.
[0011] In one embodiment, the halloysite nanotube curing accelerator may have the structure of Chemical Formula 1 below.
[0012] [Chemical Formula 1]
[0013]
[0014] In the above chemical formula 1,
[0015] R1 is a C3-C20 cycloalkylene or a C6-C20 arylene;
[0016] The above cycloalkylene and arylene may be further substituted with C1-C10 alkyl groups;
[0017] a and b are independent integers from 0 to 4.
[0018] In addition, the above chemical formula 1 may be represented by the following chemical formula 2.
[0019] [Chemical Formula 2]
[0020]
[0021] In the above chemical formula 2,
[0022] R2 to R4 are independently C1-C10 alkyls.
[0023] In addition, the present invention provides an epoxy resin composition comprising: an epoxy resin; a curing agent; and a halloysite nanotube curing accelerator according to one embodiment of the present invention.
[0024] In one embodiment, the epoxy resin may be a bisphenol-based epoxy resin.
[0025] In one embodiment, the curing agent may be one or more selected from aliphatic amine curing agents, cycloaliphatic amine curing agents, cycloaliphatic amine curing agents, and acid anhydride-based amine curing agents.
[0026] In one embodiment, the epoxy resin composition may comprise 0.1 to 10 parts by weight of a halloysite nanotube curing accelerator per 100 parts by weight of epoxy resin.
[0027] In one embodiment, the epoxy resin composition may comprise 0.1 to 5 parts by weight of a halloysite nanotube curing accelerator per 100 parts by weight of epoxy resin.
[0028] In one embodiment, the epoxy resin composition may have a curing start temperature of 160°C to 185°C as measured by a differential scanning calorimeter.
[0029] In one embodiment, the epoxy resin composition has an activation energy (E) measured by a differential scanning calorimeter a ) may be 160 kJ / mol or less.
[0030] In addition, the present invention provides a cured product including the above epoxy resin composition.
[0031] In one embodiment, the cured material may have a tensile strength of 50 MPa or more as measured by ASTM D638.
[0032] In addition, the present invention comprises the step of (a) reacting a diisocyanate compound represented by the following chemical formula 3 and an imidazole compound represented by the following chemical formula 4 at room temperature to produce an isocyanate imidazole-based compound represented by the following chemical formula 5;
[0033] (b) a step of surface treating halloysite nanotubes with an isocyanate imidazole compound prepared in step (a) under a catalyst; the present invention provides a method for preparing a halloysite nanotube curing accelerator comprising: (b) a step of surface treating halloysite nanotubes with an isocyanate imidazole compound prepared in step (a).
[0034] [Chemical Formula 3]
[0035]
[0036] [Chemical Formula 4]
[0037]
[0038] [Chemical Formula 5]
[0039]
[0040] In the above chemical formulas 3 to 5,
[0041] R1 is a C3-C20 cycloalkylene or a C6-C20 arylene;
[0042] The above cycloalkylene and arylene may be further substituted with C1-C10 alkyl groups;
[0043] a and b are independent integers from 0 to 4.
[0044] In one embodiment, the above step (b) may be performed for 2 hours or more and 48 hours or less.
[0045] In one embodiment, step (b) may be performed at 25°C to 90°C. Effects of the invention
[0046] An epoxy resin composition comprising a halloysite nanotube curing accelerator with an imidazole-based compound bonded to its surface according to the present invention can maintain high reliability and excellent mechanical properties, while simultaneously having a lower curing temperature and lower activation energy, thereby exhibiting excellent curing behavior.
[0047] The halloysite nanotube curing accelerator having an imidazole-based compound bonded to its surface according to the present invention controls the surface of the halloysite nanotube, thereby easily controlling the physical properties of the cured product obtained by curing an epoxy resin composition containing the same.
[0048] The halloysite nanotube curing accelerator with an imidazole-based compound bonded to its surface according to the present invention can be more usefully used as a material for a heterogeneous one-component epoxy adhesive composition. Brief explanation of the drawing
[0049] Figure 1 is the FT-IR result spectrum of the epoxy resin compositions according to Examples 1 to 4 and Comparative Example 2 of the present invention. Figure 2 is the EDS result spectrum of the epoxy resin composition according to Examples 1 to 4 and Comparative Example 1 of the present invention. FIG. 3 is a spectrum of the results obtained by measuring the activation energy of the epoxy resin compositions according to Examples 1 to 4 and Comparative Example 1 of the present invention. Figure 4 shows the results of specimen shape experiments of epoxy resin compositions according to Examples 1 to 4 and Comparative Examples 1 to 2 of the present invention. FIG. 5 is a TMA result spectrum comparing the degree of thermal expansion of epoxy resin compositions according to Examples 1 to 4 and Comparative Examples 1 to 2 of the present invention. Figure 6 is the FT-IR result spectrum of the isocyanate imidazole-based compound prepared in Preparation Example 1 of the present invention. Specific details for implementing the invention
[0050] The present invention is described below. Unless otherwise defined, technical and scientific terms used herein have the meanings commonly understood by those skilled in the art to which this invention pertains, and descriptions of known functions and configurations that could unnecessarily obscure the essence of the invention are omitted in the following description.
[0051] The singular form used in this specification is intended to include the plural form unless specifically indicated otherwise in the context.
[0052] Additionally, units used herein without special reference are based on weight, and, for example, units of % or ratio mean weight % or weight ratio, and weight % means the weight percentage of any one component of the total composition that occupies the composition, unless otherwise defined.
[0053] Additionally, the numerical ranges used in this specification include lower and upper limits and all values within the range, increments logically derived from the form and width of the defined range, all of which are limited values, and all possible combinations of upper and lower limits of numerical ranges defined in different forms. Unless otherwise specifically defined in this specification, values outside the numerical range that may occur due to experimental error or rounding are also included in the defined numerical range.
[0054] The term "comprising" in this specification is an open description having an equivalent meaning to expressions such as "comprising," "containing," "having," or "characterizing," and does not exclude elements, materials, or processes not additionally listed.
[0055] The terms "substituent," "radical," "group," "moiety," and "fragment" in this specification may be used interchangeably.
[0056] In this specification, "room temperature" means a temperature of 20±5℃.
[0057] The term “halloysite nanotube curing accelerator” in this specification means “halloysite nanotube curing accelerator in which an imidazole-based compound is bonded to the surface by urethane bonding.”
[0058] The term “HNT” in this specification means “Halloysite nanotube.”
[0059] The term “IM-HNT” in this specification has an equivalent meaning to “halloysite nanotubes with an imidazole-based compound bonded to their surface.”
[0060] The term "C" in this specification A -C B " means that the number of carbon atoms is A or more and B or less.
[0061] The term “alkyl” in this specification means a monovalent straight-chain or broken-chain saturated hydrocarbon radical composed only of carbon and hydrogen atoms. The alkyl may have 1 to 10 carbon atoms, 1 to 7 carbon atoms, 1 to 4 carbon atoms, or 1 to 4 carbon atoms. The alkyl includes, but is not limited to, methyl, ethyl, propyl, isopropyl, butyl, isobutyl, t-butyl, pentyl, hexyl, ethylhexyl, etc.
[0062] The term "cycloalkyl" in this specification refers to a monovalent saturated or unsaturated carbocyclic radical composed of one or more rings, which is not aromatic. The cycloalkyl may be monocyclic or a fused, spiro, or cross-linked bicyclic ring system. The cycloalkyl may have 3 to 20, preferably 4 to 10, and more preferably 4 to 7 carbon atoms.
[0063] The term “aryl” in this specification refers to an organic radical of monovalent aromatic ring derived from an aromatic hydrocarbon by the removal of one hydrogen, comprising a single or fused ring system having 6 to 20, preferably 6, ring atoms in each ring, suitably, and including forms in which multiple aryls are connected by single bonds.
[0064] The inventors of the present invention discovered a curing accelerator capable of simultaneously possessing excellent curing behavior and mechanical properties by binding an imidazole-based compound, which is mainly used as a curing accelerator for epoxy resin compositions, to the surface of halloysite nanotubes, which are nanoreinforcers, and completed the present invention.
[0065] A curing accelerator according to the present disclosure is described below.
[0066] The present invention provides a halloysite nanotube curing accelerator in which an imidazole-based compound is bonded to the surface by urethane bonding.
[0067] The halloysite nanotubes in which the reaction is performed according to one embodiment of the present invention refer to nanotube-shaped materials derived from halloysite (Al2Si2O5(OH)·2H2O) minerals, specifically, may be pulverized halloysite minerals, and more specifically, may be halloysite nanotubes having an average length of 0.3 to 5 μm and an average outer diameter of 20 to 200 nm, with hydroxyl groups substituted on the surface, but are not limited thereto.
[0068] In one embodiment, the imidazole-based compound may have an isocyanate group. The isocyanate group forms a urethane bond with a hydroxyl group naturally present on the halloysite nanotube, so that the imidazole-based compound can be bonded to the surface of the halloysite nanotube.
[0069] In one embodiment, the halloysite nanotube curing accelerator may have the structure of Chemical Formula 1 below.
[0070] [Chemical Formula 1]
[0071]
[0072] In the above formula 1, R1 is a C3-C20 cycloalkylene or a C6-C20 arylene; the cycloalkylene and arylene may be further substituted with a C1-C10 alkyl; and a and b are independently integers from 0 to 4. Preferably, a and b are independently integers from 0 to 1, and more preferably, a is 0 and b is 1.
[0073] An epoxy resin composition containing a halloysite nanotube curing accelerator having the structure of Chemical Formula 1 above can not only maintain excellent mechanical properties with high reliability, but also have excellent curing behavior by having a lower curing temperature and lower activation energy.
[0074] In one embodiment, the above chemical formula 1 may be represented by the following chemical formula 2.
[0075] [Chemical Formula 2]
[0076]
[0077] In the above chemical formula 2, R2 to R4 are independently C1-C10 alkyls. Preferably, they may be C1-C5 alkyls, and more preferably, methyls.
[0078] In addition, the present invention provides an epoxy resin composition comprising an epoxy resin, a curing agent, and a halloysite nanotube curing accelerator.
[0079] In one embodiment, the epoxy resin may have a bisphenol-type matrix structure and contain two or more glycidyl ether groups, although it is not particularly limited, and an epoxy resin composition containing the same may be preferred in that the cured product has excellent mechanical strength.
[0080] The epoxy resin having the above-mentioned bisphenol-type matrix structure may be, as an example, one or more selected from the group consisting of bisphenol A diglycidyl ether, bisphenol E diglycidyl ether, bisphenol F diglycidyl ether, bisphenol M diglycidyl ether, bisphenol S diglycidyl ether and bisphenol H diglycidyl ether, but is not limited thereto.
[0081] In one embodiment, the curing agent may preferably be an amine curing agent. More preferably, it may be an aliphatic amine curing agent, a cycloaliphatic amine curing agent, an aromatic amine curing agent, and an acid anhydride-based amine curing agent.
[0082] The above amine curing agent can be used without limitation as long as it has *-NH2, and while an epoxy resin composition containing the above amine curing agent may be preferred because it can have excellent tensile strength, an epoxy resin composition containing only the amine curing agent as a curing agent component may have inferior curing behavior as it has a higher curing temperature and activation energy.
[0083] The above aliphatic amine curing agent may be, as an example, one or more selected from diethylenetriamine (DETA), triethylenetetraamine (TETA), tetraethylenepentamine, trimethylhexamethylenediamine, 2-methylpentamethylenediamine, and isophoronediamine.
[0084] The above-mentioned cycloaliphatic amine curing agent may be, as an example, one or more selected from 1,3-bisaminomethylcyclohexane, bis(p-aminocyclohexyl)methane (PACM), norbornendiamine, 2,4-diamino-1-methylcyclohexane, 2,6-diamino-1-methylcyclohexane, and 1,2-diaminocyclohexane, and may be one or more selected from dicyandiamide, guanidine compounds, and amine curing agents to which acid anhydrides are added, which additionally contain basic functional groups such as cyano groups.
[0085] The above aromatic amine-based curing agent may be one or more selected from, for example, diaminodiphenylmethane (DDM), m-phenylenediamine, diaminodiphenylsulfone (DDS), 2,4-toluenediamine, 2,6-toluenediamine, diethyltoluenediamine, trimethylenebis(4-aminobenzoate), polytetramethyleneoxide-di-p-aminobenzoate, 2,4-diamino-3,5-diethyltoluene, 2,6-diamino-3,5-diethyltoluene, 1,2-diaminobenzene, 1,3-diaminobenzene, 1,4-diaminobenzene, diaminodiphenyl oxide, 3,3',5,5'-tetramethyl-4,4'-diaminobiphenyl, and 3,3'-dimethyl-4,4'-diaminodiphenyl.
[0086] The above acid anhydride-based amine curing agent may be, as an example, one or more selected from phthalic anhydride, maleic anhydride, trimellitic anhydride, pyromellitic anhydride, hexahydrophthalic anhydride, tetrahydrophthalic anhydride, methyl anhydride, sodium anhydride, glutaric anhydride, methylhexahydrophthalic anhydride, and methyltetrahydrophthalic anhydride, but is not limited thereto.
[0087] Preferably, the amine curing agent may be an acid anhydride-based amine curing agent having excellent curing behavior, and more preferably, a dicyandiamide curing agent, but is not limited thereto as long as it does not impair the physical properties of the epoxy resin composition containing it.
[0088] In one embodiment, the epoxy resin composition may contain 5 to 15 parts by weight of a curing agent with respect to 100 parts by weight of epoxy resin, specifically 6 to 15 parts by weight, and more specifically 8 to 13 parts by weight.
[0089] An epoxy resin composition containing a curing agent in the above-mentioned range may be preferred as it can maintain excellent tensile strength.
[0090] In one embodiment, the epoxy resin composition may contain 0.1 to 10 parts by weight of a halloysite nanotube curing accelerator per 100 parts by weight of epoxy resin, specifically 0.1 to 5 parts by weight, and more specifically 0.1 to 1.5 parts by weight.
[0091] An epoxy resin composition containing a halloysite nanotube curing accelerator in the above-mentioned range may be preferred as it can exhibit excellent mechanical properties and curing behavior.
[0092] The epoxy resin composition mixed with the above combination can maintain excellent mechanical properties while having a lower curing temperature and lower active energy, thereby exhibiting excellent curing behavior.
[0093] An epoxy resin composition according to one embodiment has a curing start temperature (T) measured by a differential scanning calorimeter. onset ) may be 160°C to 185°C, and specifically 160°C to 175°C.
[0094] An epoxy resin composition having a curing start temperature in the above range may be preferred because it can have excellent curing behavior, as the curing start temperature of the epoxy resin composition that does not contain a halloysite nanotube curing accelerator bonded to the surface of an imidazole-based compound can be 10 to 20°C lower than that of the epoxy resin composition.
[0095] An epoxy resin composition according to one embodiment has an activation energy (E) measured by a differential scanning calorimeter a ) may be 160 kJ / mol or less. This may refer to the activation energy required for the epoxy resin composition to cure.
[0096] The activation energy of the above epoxy resin composition may preferably be 150 kJ / mol or less, 140 kJ / mol or less, or 130 kJ / mol or less, and although not limited to a lower limit, it may be 100 kJ / mol or more, 110 kJ / mol or more, or 120 kJ / mol or more, and may be a value included in the above range, for example, 120 to 160 kJ / mol.
[0097] The above epoxy resin composition may have an activation energy similar to or lower than that of a conventional epoxy resin composition containing a curing accelerator, so it may be preferred as it enables curing at a low temperature and shortens the curing time until the epoxy resin composition is cured.
[0098] The above epoxy resin composition may be a one-component type and can be appropriately adjusted considering the working environment, application, and target properties. In addition, the above epoxy composition can be widely applied for uses such as adhesives, coatings, molding agents, insulators, and composite materials.
[0099] In addition, the present invention provides a cured product obtained by curing the above epoxy resin composition.
[0100] In one embodiment, the cured material may have a tensile strength of 50 MPa or more as measured by ASTM D638, preferably 60 MPa or more.
[0101] The above cured material may be preferred because, despite curing an epoxy resin composition having excellent curing behavior, it can have excellent tensile strength with high reliability.
[0102] In addition, the present invention provides a method for manufacturing a halloysite nanotube curing accelerator in which an imidazole-based compound is bonded to the surface.
[0103] A method for preparing a halloysite nanotube curing accelerator according to one embodiment of the present invention comprises: (a) a step of preparing an isocyanate imidazole-based compound represented by the following chemical formula 5 by reacting a diisocyanate compound represented by the following chemical formula 3 and an imidazole compound represented by the following chemical formula 4 at room temperature; and (b) a step of surface treating halloysite nanotubes with the isocyanate imidazole-based compound prepared in step (a) under a catalyst.
[0104] [Chemical Formula 3]
[0105]
[0106] [Chemical Formula 4]
[0107]
[0108] [Chemical Formula 5]
[0109]
[0110] In the above chemical formulas 3 to 5, R1 is a C3-C20 cycloalkylene or a C6-C20 arylene; the cycloalkylene and arylene may be further substituted with a C1-C10 alkyl; and a and b are independently integers from 0 to 4.
[0111] In one embodiment, R1 is a C3-C10 cycloalkylene or a C6-C10 arylene; the cycloalkylene and arylene may be further substituted with a C1-C5 alkyl; and a and b may be integers from 0 to 2 independently of each other.
[0112] In one embodiment, R1 is a C3-C10 cycloalkylene or a C6-C10 arylene; the cycloalkylene and arylene may be further substituted with a C1-C5 alkyl; and a may be an integer of 0 and b may be an integer of 1.
[0113] Specifically, the above manufacturing method may involve steps (a) and (b) proceeding sequentially, and may further include a step of obtaining a reactant produced in each step by removing a solvent or unreacted material through methods such as evaporation, concentration, dehydration, and filtering.
[0114] The alicyclic diisocyanate compound represented by the above chemical formula 3 can have excellent reactivity with the imidazole compound represented by the above chemical formula 4.
[0115] In another embodiment, other alicyclic diisocyanates may be used, provided that the above-mentioned alicyclic diisocyanate compound does not impair physical properties, such as 1,4-diisocyanate, trimethylhexamethylene 1,6-diisocyanate, 1-isocyanate-3,3,5-trimethyl-5-isocyanate, 1,4- or 1,3-bis(isocyanate methyl)cyclohexane (HXDI), cyclohexane 1,4-diisocyanate, 1-methylcyclohexane 2,4- or 2,6-diisocyanate, methylene dicyclohexyl, and (4,4'-, 2,4'- or 2,2'-)diisocyanate (H12MDI).
[0116] In one embodiment, the isocyanate imidazole compound represented by the above chemical formula 5 may be represented by the following chemical formula 6.
[0117] [Chemical Formula 6]
[0118]
[0119] In the above chemical formula 6, R2 to R4 are independently C1-C10 alkyls. Specifically, they may be C1-C5 alkyls, and more specifically, methyls.
[0120] The isocyanate imidazole compound represented by the above chemical formula 6 may be preferred due to its remarkable reactivity and the remarkable properties of the curing accelerator produced by binding to the surface of halloysite nanotubes.
[0121] Specifically, in step (a) above, the mass ratio of the alicyclic diisocyanate compound and the imidazole compound may be reacted in a molar ratio of 1:1, and while this range may be preferred in terms of producing an isocyanate imidazole-based compound precursor with excellent purity, it is not limited thereto.
[0122] In one embodiment, step (a) may be a step of preparing an isocyanate imidazole-based compound by dissolving an imidazole compound in a solvent and then injecting a cycloaliphatic diisocyanate compound. Specifically, the solvent is not limited to any organic solvent recognizable by those skilled in the art, but preferably may be 2-butaone. Also specifically, the injection time of the cycloaliphatic diisocyanate compound may be at a rate of 1 to 5 minutes per 1 mL, and preferably at a rate of 1 minute per 1 mL.
[0123] In one embodiment, step (b) may involve a reaction including a catalyst such as dibutyltin dilaurate, and the content of the catalyst may be used without limitation as long as it is at a level recognizable by those skilled in the art.
[0124] In one embodiment, the halloysite nanotubes of step (b) may be a dispersion that is dissolved in a solvent and then ultrasonically dispersed. Specifically, dispersion may be performed for 1 minute to 3 hours, and more specifically, for 10 minutes to 60 minutes.
[0125] In one embodiment, step (b) may be a step of adding the isocyanate imidazole-based compound prepared in step (a) to the halloysite nanotube dispersion and stirring.
[0126] In one embodiment, the above step (b) may be performed for 2 hours or more and 48 hours or less, preferably for 12 hours or more and 36 hours or less, and more preferably for 20 hours or more and 28 hours or less.
[0127] In one embodiment, step (b) may be performed at 25°C to 90°C, preferably at 50°C to 80°C, and more preferably at 65°C to 75°C.
[0128] Through the above steps, the isocyanate group of the imidazole compound forms a urethane bond with the hydroxyl group naturally present on the halloysite nanotube, so that the imidazole compound can be bonded to the surface of the halloysite nanotube.
[0129] The following examples further describe in detail a halloysite nanotube curing accelerator having an imidazole-based compound bonded to its surface according to the present invention, a method for manufacturing the same, and an epoxy resin composition containing the same. However, the following examples are merely references for the detailed description of the present invention and are not limited thereto, and the present invention may be embodied in various forms. Furthermore, unless otherwise defined, all technical and scientific terms have the same meaning as generally understood by one of the art to which the present invention pertains. Additionally, the terms used in the description of the present invention are intended merely to effectively describe specific examples and are not intended to limit the present invention.
[0130] [measurement method]
[0131] 1. Differential Scanning Calorimetry
[0132] The epoxy resin composition was heated from 25 ℃ to 250 ℃ using a differential scanning calorimeter (DSC Q2000, TA Instruments) at a heating rate of 10 ℃ / min, and the curing start temperature (T onset ) and maximum curing temperature (T peak ) was measured. Activation energy (E a T ) is measured under nitrogen conditions at heating rates of 2, 5, 10, and 20 ℃ / min Peak It was calculated using the value and the Kissinger formula below.
[0133]
[0134] 2. Tensile strength measurement
[0135] Measurements were taken using a universal testing machine (UTM 5982, INSTRON), and tensile strength, Young's modulus, and tensile strain were measured according to ASTM D 638. Specimens measuring 150 mm x 13 mm x 3 mm were prepared and tested.
[0137] [Preparation Example 1] Synthesis of Isocyanate-Imidazole Compounds
[0138] After dissolving 3.3 g of Imidazole in 50 mL of 2-Butanone, the mixture was slowly injected into 9.8 g of Isophorone Diisocyanate at a rate of 1 mL / min using a syringe pump, and stirred at 600 RPM at room temperature for 24 hours to obtain an isocyanate imidazole compound. The FT-IR results of the structure of the prepared compound are shown in Figure 6 below.
[0139]
[0140] [Preparation Example 2] Preparation of Halloysite Nanotube (HNT) Curing Accelerator (8hr)
[0141] 1 g of HNT was dispersed in 50 mL of 2-Butanone for 30 minutes using an ultrasonic disperser (VCX-500, Sonics & Materials, Inc., USA). 0.08 g of Dibutyltin Dilaurate and the above HNT dispersion were added to the solution synthesized in Example 1, and the mixture was stirred at 600 RPM for 8 hours at 70 ℃. Subsequently, the HNT was washed with Acetone using a centrifuge and dried in a vacuum oven at 40 ℃ for 24 hours to obtain a halloysite nanotube curing accelerator.
[0142] [Preparation Example 3] Preparation of Halloysite Nanotube (HNT) Curing Accelerator (16hr)
[0143] In the above Preparation Example 2, the same was prepared except that the HNT dispersion was stirred for 16 hours after addition.
[0144] [Preparation Example 4] Preparation of Halloysite Nanotube (HNT) Curing Accelerator (24hr)
[0145] In the above Preparation Example 2, the same was prepared except that the HNT dispersion was stirred for 24 hours after addition.
[0146] [Preparation Example 5] Preparation of Halloysite Nanotube (HNT) Curing Accelerator (48hr)
[0147] In the above Preparation Example 2, the same was prepared except that the HNT dispersion was stirred for 48 hours after addition.
[0148] [Comparative Manufacturing Example 1] Preparation of Halloysite Nanotube (HNT) Curing Accelerator (p-HNT)
[0149] 1 g of HNT was dispersed in 50 mL of 2-Butanone for 30 minutes using an ultrasonic disperser (VCX-500, Sonics & Materials, Inc., USA). Subsequently, the HNT was washed with acetone using a centrifuge and dried in a vacuum oven at 40 ℃ for 24 hours to obtain a halloysite nanotube curing accelerator.
[0151] Preparation of epoxy resin composition
[0152] [Example 1]
[0153] An epoxy resin composition was prepared by mixing 100 g of bisphenol A diglycidyl ether (DGEBA, Momentive, EPIKOTE 828), 11.24 g of dicyandiamide (DICY), and 1 g of the curing accelerator prepared in Preparation Example 2 at room temperature under vacuum for 30 minutes using a planetary mixer (PDM-300V, KMtech Co., Ltd., Korea).
[0154] [Example 2]
[0155] In the above Example 1, an epoxy resin composition was prepared in the same way except that the curing accelerator was replaced with the curing accelerator of Preparation Example 3.
[0156] [Example 3]
[0157] In the above Example 1, an epoxy resin composition was prepared in the same way except that the curing accelerator was replaced with the curing accelerator of Preparation Example 4.
[0158] [Example 4]
[0159] In the above Example 1, an epoxy resin composition was prepared in the same manner except that the curing accelerator was replaced with the curing accelerator of Preparation Example 5.
[0160] [Comparative Example 1]
[0161] In the above Example 1, an epoxy resin composition was prepared in the same manner except that the curing accelerator of Comparative Example 1 was replaced with a curing accelerator of 1 wt% relative to the epoxy resin, and 0.21 g of 2-methylimidazole was added as an accelerator.
[0162] [Comparative Example 2]
[0163] In the above Example 1, an epoxy resin composition was prepared in the same way except that no curing accelerator was added.
[0164] The epoxy resin compositions of the above examples and comparative examples are shown in Table 1 below.
[0165] EPIKOTE 828(g) IM-HNT(g) p-HNT(g) DICY(g) IM promoter (g) Example 1 100 1 - 11.24 - Example 2 100 1 - 11.24 - Example 3 100 1 - 11.24 - Example 4 100 1 - 11.24 - Comparative Example 1 100 - 1 11.24 0.21 Comparative Example 2 100 - - 11.24 - Comparative Example 3 100 - 1 11.24 -
[0166] Experimental Example 1: Confirmation of Surface Composition (FT-IR)
[0167] To confirm the surface composition of HNT according to surface treatment time, changes in surface functional groups were confirmed through Fourier transform infrared spectroscopy and are shown in Figure 1.
[0168] 1800 and 1200 cm -1 By intensively comparing the intervals, it was confirmed that a peak due to Al2OH- appeared, and at 1100 cm⁻¹ -1It was confirmed that a Si-O-Si peak appeared in the vicinity.
[0169] Upon surface treatment with nitrogen and phosphorus, the Al2OH- peak decreased sharply, and at 3300 cm⁻¹ -1 at NH, 2800 cm -1 and 1600 cm -1 At P-OH, 1100 cm -1 It was confirmed that a peak due to P=O occurred, and through this, it was confirmed that phosphorus and nitrogen are present on the surface of HNT.
[0171] Experimental Example 2: Confirmation of Surface Elemental Composition (EDS)
[0172] The surface elemental composition of HNT according to surface treatment time was confirmed via EDS and is shown in Table 2 and Figure 2 below. It was confirmed that the nitrogen content increased to approximately 25% as the surface treatment time increased, thereby confirming that the imidazole content increased. When the surface treatment homogeneity was checked using the Coefficient of Variation, it was confirmed that there was almost no change as the surface treatment time increased after 24 hours, thereby confirming that the optimal surface treatment time is 24 hours.
[0173] Elemental content (atomic%) Al Si N Comparative Example 1 40.5 59.5 0.0 Example 1 73.9 20.8 5.3 Example 2 66.8 22.7 10.5 Example 3 46.1 29.4 24.5 Example 4 45.7 29.5 25.6
[0174] Experimental Example 3: T onset and T peak Measurement (DSC)
[0175] Table 3 below shows the curing start temperature (T) of the epoxy composition measured using a differential scanning calorimeter. onset ) and maximum curing temperature (T peak This represents the result.
[0176] T Onset (℃) T Peak (℃) Comparative Example 1 127.8 156.9 Comparative Example 2 191.6 201.8 Example 1 184.7 193.3 Example 2 180.4 192.3 Example 3 172.4 188.5 Example 4 170.5 184.4
[0177] T of the compositions OnsetIt was confirmed that the temperature decreased from approximately 192 °C to 170 °C as the surface treatment time increased, confirming that the amount of imidazole present on the surface of HNT increased and the curable temperature decreased as the surface treatment time increased. However, from 24 hours onwards, T Onset It can be seen that the amount of change decreases rapidly, indicating that 24-hour surface treatment is suitable.
[0178] Experimental Example 4: Activation Energy (E a ) measurement
[0179] T Peak E calculated using the value and the Kissinger equation a This is shown in Fig. 3 and Table 4 below.
[0180] Activation energy E a (kJ / mol) Comparative Example 1 149.35 Comparative Example 2 181.67 Comparative Example 3 179.52 Example 1 157.71 Example 2 143.32 Example 3 135.08 Example 4 129.30
[0181] As surface treatment time increases, activation energy (E a It was confirmed that the amount of ) continuously decreases, and that the curing acceleration effect is superior to conventional curing accelerators when the surface treatment time is 8 hours or longer.
[0182] Experimental Example 5: Tensile Strength Measurement
[0183] Table 5 below shows the tensile strength of the epoxy composition.
[0184] Comparative Example 2 Comparative Example 1 Example 1 Example 2 Example 3 Example 4 tensile strength 63.99(7.61) 1 61.52(1.62) 1 56.33(9.58) 1 60.62(4.14) 1 63.98(1.46) 1 61.44(2.44) 1
[0185] ( 1 Standard deviation)
[0186] In the case of Comparative Example 2, which did not contain HNT and a hardening accelerator, a very high tensile strength of 63.99 MPa was exhibited compared to other conditions, but it was confirmed that the error was very large.
[0187] On the other hand, when a curing catalyst was included, the tensile strength decreased slightly (63.99 → 61.52 MPa), but the error in mechanical properties decreased, and it was confirmed that reliability increased.
[0188] It was confirmed that the shorter the surface treatment time of IM-HNT, the greater the decrease in mechanical properties and the larger the error, indicating that IM-HNT hindered curing and reduced the properties. Conversely, it was confirmed that IM-HNT treated for 24 hours acted as a catalyst, leading to an increase in mechanical properties and a decrease in error. When surface treatment was performed for more than 24 hours, the properties decreased again; this suggests that the phenomenon occurred because the surface was treated with an excessive amount of IM, weakening the interfacial strength between HNT and epoxy.
[0190] Experimental Example 6: Confirmation of morphology and degree of crosslinking through specimens
[0191] The curing accelerators prepared through Examples 1 to 4 and Comparative Examples 1 to 2 were examined through specimens to confirm their shape, as shown in FIG. 4. It was confirmed that the specimen of Comparative Example 2 (Neat), in which no curing catalyst was included, appeared generally transparent, and that it exhibited a milky white color in some opaque sections.
[0192] To confirm the degree of crosslinking according to the section, the degree of thermal expansion and the change in slope of the specimen containing Comparative Example 2 from room temperature to 250°C were compared via Thermomechanical Analysis (TMA) and are shown in Fig. 5 and Table 6 below. Through this, it was confirmed that the transparent section (A, blue) exhibited a higher coefficient of thermal expansion with increasing temperature than the opaque section (B, red). In addition, through the section of slope change, T for each section g When checking, it was observed that the transparent section (A, blue) was about 12°C lower than the opaque section (B, red), indicating that the degree of crosslinking is higher in the opaque section.
[0193] Section Dimension Change ( μ m / ℃) T g (℃) Before T g After T g Transparent section (A) 0.213 0.511 127.69 Opaque section (B) 0.231 0.510 139.16
[0194] Comparative Example 1 ( pWhen the catalyst of -HNT 1 wt%) was added, it was confirmed that the specimen was milky white throughout, and as the surface treatment time of IM-HNT increased, the region showing an opaque milky white gradually increased.
[0195] Through this, it can be seen that the degree of crosslinking due to the catalytic effect increases as the degree of surface treatment increases.
[0197] Accordingly, the epoxy resin composition comprising a halloysite nanotube curing accelerator with an imidazole-based compound bonded to the surface of the present invention can be prepared as specific examples in Examples 1 to 4, and preferably, it was confirmed that the epoxy resin composition comprising Example 4 can maintain excellent mechanical properties with high reliability while having excellent curing behavior by having a lower curing temperature and lower activation energy.
[0198] In other words, the physical properties of the above-mentioned curing accelerator can be controlled according to surface treatment conditions, and since the control of such physical properties is easy, it can be appropriately applied to industrial fields where such physical properties are essential.
[0199] In addition, the halloysite nanotube curing accelerator with an imidazole-based compound bonded to its surface according to the present invention can be more usefully used as a material for a heterogeneous one-component epoxy adhesive composition.
[0200] As described above, the present invention has been explained by specific details, limited embodiments, and comparative examples; however, these are provided merely to aid in a more comprehensive understanding of the invention, and the invention is not limited to the above embodiments. Those skilled in the art can make various modifications and variations from this description.
[0201] Accordingly, the scope of the present invention is not limited to the described embodiments, and all things equivalent to or having equivalent variations to the claims set forth below, as well as the claims set forth below, shall be considered to fall within the scope of the concept of the present invention.
Claims
Claim 1 A halloysite nanotube curing accelerator having an imidazole-based compound bonded to its surface via urethane bonding, and having the structure of Chemical Formula 1 below. [Chemical Formula 1] In the above chemical formula 1, R1 is a C3-C10 cycloalkylene or a C6-C10 arylene; the cycloalkylene and arylene may be further substituted with a C1-C10 alkyl group; and a and b are independently integers from 0 to 4. Claim 2 A halloysite nanotube curing accelerator according to claim 1, wherein the imidazole-based compound has an isocyanate group. Claim 3 delete Claim 4 A halloysite nanotube curing accelerator according to claim 1, wherein the above chemical formula 1 is represented by the following chemical formula 2.[Chemical Formula 2] In the above chemical formula 2, R2 to R4 are independently C1-C10 alkyls. Claim 5 An epoxy resin composition comprising: an epoxy resin; a curing agent; and a halloysite nanotube curing accelerator according to any one of claims 1, 2 and 4. Claim 6 An epoxy resin composition according to claim 5, wherein the epoxy resin is a bisphenol-based epoxy resin. Claim 7 An epoxy resin composition according to claim 5, wherein the curing agent is one or more selected from aliphatic amine curing agents, alicyclic amine curing agents, cyclic amine curing agents, and acid anhydride-based amine curing agents. Claim 8 In claim 5, the epoxy resin composition comprises 0.1 to 10 parts by weight of a halloysite nanotube curing accelerator per 100 parts by weight of epoxy resin. Claim 9 In claim 5, the epoxy resin composition comprises 0.1 to 5 parts by weight of a halloysite nanotube curing accelerator per 100 parts by weight of epoxy resin. Claim 10 In claim 5, the epoxy resin composition is an epoxy resin composition having a curing start temperature of 160°C to 185°C as measured by a differential scanning calorimeter. Claim 11 In claim 5, the epoxy resin composition has an activation energy (E) measured by a differential scanning calorimeter a An epoxy resin composition having a ) of 160 kJ / mol or less. Claim 12 A cured product including the epoxy resin composition of claim 5. Claim 13 In Clause 12, the above-mentioned cured material is a cured material having a tensile strength of 50 MPa or more as measured by ASTM D638. Claim 14 (a) a step of preparing an isocyanate-imidazole compound represented by the following chemical formula 5 by reacting a diisocyanate compound represented by the following chemical formula 3 and an imidazole compound represented by the following chemical formula 4 at room temperature; (b) a step of surface treating halloysite nanotubes with the isocyanate-imidazole compound prepared in step (a) under a catalyst; comprising a method for preparing a halloysite nanotube curing accelerator. [Chemical Formula 3] [Chemical Formula 4] [Chemical Formula 5] In the above chemical formulas 3 to 5, R1 is a C3-C10 cycloalkylene or a C6-C10 arylene; the cycloalkylene and arylene may be further substituted with a C1-C10 alkyl; and a and b are independently integers from 0 to 4. Claim 15 A method for manufacturing a halloysite nanotube curing accelerator according to claim 14, wherein step (b) is performed for 2 hours or more and 48 hours or less. Claim 16 A method for manufacturing a halloysite nanotube curing accelerator according to claim 14, wherein step (b) is performed at 25°C to 90°C.
Citation Information
Patent Citations
Method for grafting curing agent imidazole on surface of carbon fiber
CN109385891A
Conductive silver adhesive long in room-temperature use time and capable of being cured at low temperature and preparation method thereof
CN112080221A
Epoxy resin composition and preparation method thereof
CN116515250A
